Comparative evaluation of Xpert MTB/RIF assay with multiplex polymerase chain reaction for the diagnosis of tuberculous meningitis. (December 2018) - Sharma, Kusum; Sharma, Megha; Chaudhary, Lokesh; Modi, Manish; Goyal, Manoj; Sharma, Navneet; Sharma, Aman; Jain, Anumiti; Dhibar, Deba Prasad; Jain, Kajal; Khandelwal, Niranjan; Ray, Pallab; et al.
Abstract: Background: Rapid and specific diagnosis of tuberculous meningitis (TBM) is of paramount importance to decrease morbidity and mortality. Therefore, the present study was undertaken to compare the efficacy of Xpert MTB/RIF assay (GXpert) and multiplex PCR (MPCR) using three targets (IS 6110, MPB64 and protein B) for diagnosing tuberculous meningitis. Methods: GXpert and MPCR were performed on cerebrospinal fluid samples of 225 patients out of which 80 were culture-positive confirmed cases of TBM, 100 were 'suspected' cases of TBM and 45 were non-TBM controls. rpo B gene sequencing was done for diagnosing rifampicin (Rif) resistance in all positive cases. Results: GXpert and MPCR were positive in 91/180 (50.5%) and 157/180 (87.2%) confirmed or suspected TBM patients respectively. Both the tests were negative in all 45 controls. Rif resistance was detected in 14 cases by GXpert and in 13 cases by MPCR. Rif resistance was confirmed in 13 cases with rpo B gene sequencing. There was one case of false Rif resistance detected by GXpert which was Rif susceptible on rpo B gene sequencing. Cost of doing MPCR was less than USD1 whereas GXpert required USD10 per isolate. Conclusion: MPCR has a higher sensitivity than GXpert for diagnosing TBM. MPCR is a robust and cost effective method for diagnosis of TBM in low-resource and high-endemic countries.